Research prospects of user information detection from encrypted traffic of mobile devices - Tengfei ZHANG; Shunzheng YU (Tongxin xuebao)
Encrypted traffic analysis of mobile devices can obtain multiple types of user information in an active or passive way, which provides protection for network security management and user privacy protection.The basic principles and key methods of data collection, feature selection, models and methods, and evaluation systems involved in these user information detection were analyzed and summarized.The problems in the existing projects were summarized, as well as the future research directions and challenges.